2002
DOI: 10.1242/jcs.115.13.2689
|View full text |Cite
|
Sign up to set email alerts
|

Cas, Fak and Pyk2 function in diverse signaling cascades to promote Yersinia uptake

Abstract: The interplay between pathogen-encoded virulence factors and host cell signaling networks is critical for both the establishment and clearance of microbial infections. Yersinia uptake into host cells serves as an in vitro model for exploring how host cells respond to Yersinia adherence. In this study, we provide insight into the molecular nature and regulation of signaling networks that contribute to the uptake process. Using a reconstitution approach in Fak-/- fibroblasts, we have been able to specifically ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(12 citation statements)
references
References 94 publications
2
10
0
Order By: Relevance
“…Because Yersinia InvA can mediate epithelial cell invasion, we performed antibiotic protection assays to assess if InvL performs a similar function ( 54 – 58 ). However, internalization was not observed in any of the cell lines tested, and immunofluorescence assays following epithelial cell infection confirmed UPAB1 is not invasive ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because Yersinia InvA can mediate epithelial cell invasion, we performed antibiotic protection assays to assess if InvL performs a similar function ( 54 – 58 ). However, internalization was not observed in any of the cell lines tested, and immunofluorescence assays following epithelial cell infection confirmed UPAB1 is not invasive ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this, Bruce-Staskal, et al . (2002) have shown that Yersinia uptake involved a complex interplay in Cas, FAK, Pyk2 and Rac1 cell signalling (42). Through inhibition of Pyk2 phosphorylation, we first demonstrated that AIEC phagocytosis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Because Yersinia InvA can mediate epithelial cell invasion, we performed antibiotic protection assays to assess if InvL performs a similar function (53)(54)(55)(56)(57). However, internalization was not observed in any of the cell lines tested, and immunofluorescence assays following epithelial cell infection confirmed UPAB1 is not invasive (Fig.…”
Section: Invl Facilitates Upab1 Adhesion To Bladder and Kidney Epithe...mentioning
confidence: 99%